Variability of study skills in higher education: The case of Rwanda undergraduate students at National Police College - Mukingambeho, D.; Nzahabwanayo, S.; Gabriel, N.; Nzabalirwa, W. (South African Journal of Higher Education, 2021)
This study extends knowledge production about students’ study skills in higher education. It is intended to unpack variations among undergraduate students’ study skills based on demographic characteristics. The article uses a comparative cross-sectional design drawing on a survey questionnaire distributed among 398 students of three programs of study at the University of Rwanda (UR), National Police College (NPC). These are Professional Police Studies (PPS), Law and Computer Science (CS) with the option of Information Security. Results indicate that students’ features primarily gender, age, marital status, year of study, program of study and working experience are relevant categories to study skills. These features were found to have an effect on all study skills investigated except gender which influence test preparation and test-taking only. We argue that strategies for improving study skills at all levels of higher education should take cognizance of students’ demographic features.